미용업의 동종업종 간 거리제한 도입의 필요성에 관한 연구 - 김신미; Sin-mi Kim; 나명석; Myung-suk Na (한국미용학회지, 2022)
Recently, there has been a shift in beauty market from beauty salon-led market where demand was higher than supply to customer-driven market when demand is lower than supply. At present, beauty salons are already saturated. Under excessive competitions, furthermore, profitability has significantly decreased. Despite high competitiveness and great ripple effects, however, domestic beauty industry is undergoing some difficulties due to industry polarization and absence of a decent system. Considering a necessity of protecting right to life and goodwill for beauty businesses and establishing the ground for co-prosperity, therefore, this study targeted to minimize damages resulting from business overlapping and find a way for co-prosperity through a questionnaire survey on the awareness of model transactions against franchise chain and mom-and-pop beauty salon managers, and the results found the followings: According to detailed analysis on the current situations of beauty industry, 91.7% said that supply is now greater than demand. In addition, 80.6% understood a necessity of adopting minimum distance among businesses in beauty industry because of decrease in sales and difficulties in recruitment difficulties. Therefore, this study aimed to suggest such necessity and improve value orientation in beauty industry.